Assessing the Risk of APOE-ϵ4 on Alzheimer’s Disease Using Bayesian Additive Regression Trees - Xia, Yifan; Liang, Baosheng (Mathematics (Basel), 2023)
Alzheimer’s disease (AD) affects about a tenth of the population aged over 65 and nearly half of those over 85, and the number of AD patients continues to grow. Several studies have shown that the ϵ4 variant of the apolipoprotein E (APOE) gene is potentially associated with an increased risk of AD. In this study, we aimed to investigate the causal effect of APOE-ϵ4 on Alzheimer’s disease under the potential outcome framework and evaluate the individualized risk of disease onset for APOE-ϵ4 carriers. A total of 1705 Hispanic individuals from the Washington Heights-Inwood Columbia Aging Project (WHICAP) were included in this study, comprising 453 APOE-ϵ4 carriers and 1252 non-carriers. Among them, 265 subjects had developed AD (23.2%). The non-parametric Bayesian additive regression trees (BART) approach was applied to model the individualized causal effects of APOE-ϵ4 on disease onset in the presence of right-censored outcomes. The heterogeneous risk of APOE-ϵ4 on AD was examined through the individualized posterior survival probability and posterior causal effects. The results showed that, on average, patients carrying APOE-ϵ4 were 0.968 years younger at onset than those with non-carrying status, and the disease risk associated with APOE-ϵ4 carrying status was 3.9% higher than that for non-carrying status; however, it should be noted that neither result was statistically significant. The posterior causal effects of APOE-ϵ4 for individualized subjects indicate that 14.41% of carriers presented strong evidence of AD risk and approximately 38.65% presented mild evidence, while around 13.71% of non-carriers presented strong evidence of AD risk and 40.89% presented mild evidence. Furthermore, 79.26% of carriers exhibited a posterior probability of disease risk greater than 0.5. In conclusion, no significant causal effect of the APOE-ϵ4 gene on AD was observed at the population level, but strong evidence of AD risk was identified in a sub-group of APOE-ϵ4 carriers.